Life AfTER covid-19 (LATER-19): a protocol for a prospective, longitudinal, cohort study of symptoms, physical function and psychological outcomes in the context of a pandemic - Edgar, Dale W; Gittings, Paul; Van Der Lee, Lisa; Naylor, Louise; Maiorana, Andrew; Jacques, Angela; Cavalheri, Vinicious (2020)
Introduction